A Study on Development and Validation of HPTLC Methods of New Pharmaceutical Drugs: Development and Validation of HPTLC Methods for Pharmaceutical Drugs (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A straightforward unrivaled slight layer chromatography (HPTLC) has been made and approved for affirmation of sunitinib malate and potential debasements. The precedents were associated in sorts of groups on aluminum HPTLC plate pre-secured with silica gel and were detached using dichloromethane methanol toluene smelling salts game plan as the convenient stage. Sunitinib malate was by and large confined from debasements including E-isomer, sunitinib N-oxide and pollution B with a support factor (RF) of 0.35±0.02. Quantitative examination of sunitinib was finished using a convenient stage involving dichloromethane methanol smelling salts plan, RF regard was 0.53±0.02 for Z isomer. Disclosure was performed densitometrically in absorbance mode at 430 nm. This procedure was found to convey sharp, symmetrical, and especially settled apexes. Direct relationship with the coefficients of confirmation > 0.99 was practiced over the obsession scope of 27.34 to 437.5 ngspot. This system gives healthy, replicable and accurate results with satisfactory affectability.